Building a performance measurement internal auditing framework for the ISO 9001 quality management system - Gutierrez Alcantara, Flor Monica (2013)
During the last two decades, ISO 9000 standards have become one of the most important management approaches in the world. Currently, the standards are used by more than one million companies in more than 170 countries. ISO 9001 audits are the most widely used performance measurement (PM) method to assess ISO 9001 quality management systems (QMS). However, in recent years the effectiveness of ISO 9001 quality auditing has been questioned for: (1) only focusing on compliance; (2) failing to detect problems in products and processes; (3) failing to predict QMS failures; and (4) failing to provide added value to organisations.